Family-Based Model of Children's Sexual Abuse and Violence Prevention Using Maternal Responsiveness Method at Jember Regency - Dewi Rokhmah; Tantut Susanto; Jihan Muna Salma; Andriani Metasari Br Limbong (NurseLine Journal, 2023)
The high rate of sexual violence against children means that children in Indonesia are at risk of becoming victims of child sexual abuse and violence. The growth and development of children is related to the condition of the family including their parents, their father and mother. One of the many health outcomes associated with maternal responsiveness is cognitive and psychosocial effects where maternal responsiveness greatly influences child development. This study to develop a community-based model for the prevention of child sexual abuse and violence with the maternal responsiveness method in realizing a healthy Jember Regency. This study used an observational analytic research design with a cross-sectional study method. The population in this study were people in Rambipuji District with families who had children who were victims of sexual violence. The sample size was calculated based on the rule of the thumb formula in SEM (Structural Equation Modeling) resulting in 118 respondents. The sample was determined by using multistage random sampling technique with the sampling stage from sub-districts to clusters or RTs. Data analysis used univariate analysis and multivariate analysis used logistic regression test. Maternal factors in the good category had an effect on responsiveness by 26,750 times compared to the factors of the bad category. Based on the results of the study, the results showed that children's factors consisting of children's health status, children's gross motor system, children's fine motor systems, children's socialization in language had an effect on preventing children from sexual violence, namely children. mentally healthy and socially healthy. The majority of respondents are 26-45 years old, highly educated, work, and Javanese. The results of multivariate analysis using logistic regression, show that there is an influence between maternal factors responsiveness and there is an influence between child factors and the avoidance of children from sexual violence.